A multi-center study on the association between serum magnesium levels and allostatic load in hemodialysis patients - Zhang, Yingxin; Yang, Zhengling; Yang, Huan; Li, Xiuyong; Liu, Zhi; Bai, Youwei; Qian, Guangrong; Wu, Han; Li, Ji; Guo, Yuwen; Yang, Shanfei; Chen, Lei; et al. (Frontiers in Physiology, 2022)
Objective: Serum magnesium (Mg2+) levels are associated with insulin resistance, hypertension, lipid abnormalities, and inflammation. However, limited studies have indicated the relationship between Mg2+ and multiple system index. The purpose of this study was to investigate the association between Mg2+ and allostatic load (AL) in hemodialysis patients. Methods: A cross-sectional survey was conducted in hemodialysis patients from different centers in Anhui province, China between January and December 2020. A total of 3025 hemodialysis patients were recruited. Their clinical data were measured before hemodialysis. Information was collected by an online self-reported questionnaire and medical record. Serum Mg2+ was divided into 3 groups by tertiles. A score of AL greater than or equal to 3 was defined as high AL. Binary logistic regression model was applied to examine the relationship between serum Mg2+ and AL. Result: A total of 1222 patients undergoing hemodialysis were included, 60% of whom were males (733/1222). The mean (standard deviation) age of patients was 55.90 (12.75). The median level of serum Mg2+ was 1.22 mmol/L. The rate of high AL level was 23.4%. Serum Mg2+ was negatively correlated with body mass index, fasting blood glucose (Glu), and C reactive protein and positively correlated with high-density lipoprotein, low-density lipoprotein, total cholesterol, diastolic blood pressure (DBP), and serum phosphorus. After adjusting for gender, anxiety, diabetes, family residence, lipid-lowering agents, Antihypertensive, albumin and Glu, binary logistic regression model showed that patients with lower levels of serum Mg2+ were more likely to be with high AL (OR for T1 group of serum Mg2+:1.945, 95%CI: 1.365-2.773; OR for T2 group of serum Mg2+:1.556, 95%CI: 1.099-2.201). Conclusions: Our data support the hypothesis that higher serum Mg2+ concentrations may contribute to lower health risk in hemodialysis populations. Further randomized controlled trials and cohort studies are warranted to verify whether Mg2+ supplementation could be a part of routine examinations in hemodialysis populations.